The secret of the wooden lady - Keene, Carolyn (New York : Grosset & Dunlap, 1995)
Nancy Drew and her friends visit an old clipper ship in Boston harbor and help Captain Easterly uncover a mystery.
Keywords: Women detectives -- Juvenile fiction; Detective and mystery fiction